If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2l + 2w = 50 Solving 2l + 2w = 50 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-2w' to each side of the equation. 2l + 2w + -2w = 50 + -2w Combine like terms: 2w + -2w = 0 2l + 0 = 50 + -2w 2l = 50 + -2w Divide each side by '2'. l = 25 + -1w Simplifying l = 25 + -1w
| 6(-6x+10)=348 | | 2(-3k-2)=-58 | | 4(-2+2x)=64 | | 5(3+3a)=45 | | 4(6-3d)=-108 | | 5(7d-5)=80 | | 3(-3-d)=24 | | 6n+3=-3n+30 | | -k+6=42+3k | | 4w+9=2w+29 | | 9+4d=3d+12 | | 6+7a=3a-22 | | 6w+9=33+3w | | x^2+3x+4=8 | | 44/7+88=b | | -2-5x=x-44 | | 9+7x=x+15 | | d+7=40+4d | | 3d-9=0+6d | | 5a+6=-54-7a | | 3m-9=m-1 | | 3d-8=-5+6d | | 3y^2-13y+4= | | -10(-9x)= | | x^2+8x-11=9x-5 | | 62/7*20=y | | -10(9x)= | | 6m-5=4m+17 | | -m-10=-3+6m | | w-5=6w-50 | | 3+3a=5a-5 | | 4d+6=-14+6d |